A practical guide to pediatric emergency medicine : caring for children in the emergency department - 4 0 16; 1964- Amieva-Wang, N. Ewen; 5 (Cambridge ;;New York : Cambridge University Press, 2011)
This practical guide is written for the emergency department physician who cares for adults and children concurrently and provides all the information needed to diagnose and treat a wide variety of common and uncommon pediatric disorders. Each chapter takes a clinical perspective, emphasizing differences in adult and pediatric disease process and management. Key facts, special considerations, and pearls and pitfalls are highlighted, providing rapid access to vital knowledge in emergency situations. Sections are dedicated to specific pediatric populations, including neonates, adolescents, and children with special health care needs. High-quality photographs, illustrations and diagrams enhance the text throughout and tutorials cover pediatric imaging, pediatric EKG interpretation, procedural sedation, and procedures. Written by pediatric and emergency medicine specialists and subspecialty experts, this is a must-have text for emergency medicine physicians and trainees, as well as family practice health care practitioners--Provided by publisher.
Machine generated contents note: Part I. Resuscitation; Part II. Allergy; Part III. Cardiac Emergencies; Part IV. Dental Emergencies; Part V. Dermatology; Part VI. Ear, Nose, Throat; Part VII. Endocrine Emergencies; Part VIII. Environmental; Part IX. Fluids and Electrolytes; Part X. Gastrointestinal Emergencies; Part XI. Gynecologic Emergencies; Part XII. Hematology and Oncology Emergencies; Part XIII. Immunologic Emergencies; Part XIV. Infectious Disease Emergencies; Part XV. Musculoskeletal System; Part XVI. Neurology; Part XVII. Ophthalmology; Part XVIII. Psychiatric Emergencies.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; methods;methods -- Pediatric emergencies;Critical care medicine;Emergencies;Child.;Critical Care;Emergency Treatment;Infant. -- 20 -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks.;Handbooks.;Handbooks.; 20; 2